1997
DOI: 10.1111/j.1365-2249.1997.tb08316.x
|View full text |Cite
|
Sign up to set email alerts
|

IgA from HIV+ haemophilic patients triggers intracellular signals coupled to the cholinergic system of the intestine

Abstract: SUMMARYIgA was obtained from HIV-infected haemophilic patients and the intracellular signals triggered by its reaction with isolated rat intestinal strips were studied. HIV+IgA stained intestinal microvilli with a granular immunofluorescence pattern and bound to the muscarinic acetylcholine receptor (mAChR), displacing the specific muscarinic cholinergic antagonist QNB in a non-competitive manner. It triggered the signals that are the consequence of mAChR stimulation in the intestine. Thus, it decreased CAMP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Our data infer that the reduced compliance with these antidepressants may have a biological basis, in particular an apparent increase in cholinergic sensitivity in the HIV/AIDS population. Indeed, cholinomimetic antibodies of the immunoglobulin (IgA) class are present in HIV/AIDS patients [ 58 , 59 ], suggesting that these patients may indeed be hypersensitive to drugs with activity on the cholinergic system [ 60 ]. Importantly, TCA and paroxetine non-compliance with TCAs and paroxetine can evoke a cholinergic overdrive [ 57 , 61 ], which may augment the hyper-cholinergic state present in HIV/AIDS patients, leading to a greater adverse experience and subsequent non-compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Our data infer that the reduced compliance with these antidepressants may have a biological basis, in particular an apparent increase in cholinergic sensitivity in the HIV/AIDS population. Indeed, cholinomimetic antibodies of the immunoglobulin (IgA) class are present in HIV/AIDS patients [ 58 , 59 ], suggesting that these patients may indeed be hypersensitive to drugs with activity on the cholinergic system [ 60 ]. Importantly, TCA and paroxetine non-compliance with TCAs and paroxetine can evoke a cholinergic overdrive [ 57 , 61 ], which may augment the hyper-cholinergic state present in HIV/AIDS patients, leading to a greater adverse experience and subsequent non-compliance.…”
Section: Discussionmentioning
confidence: 99%
“…These Abs activate M 2 and M 3 muscarinic receptors intracellular signals respectively, promoting agonistic functions that impaired patients' conditions [16,17]. We had previously reported the presence of IgA Abs in the sera of haemophilic HIV+ patients that interact with ileal muscarinic receptors exerting parasympathetic actions on ileal motility by inducing IP3 and prostaglandin E 2 synthesis [18]. We observed that IgA-HIV+ was a more potent stimulus than CARB to activate ileal cholinoceptors in the same manner than ETB IgG, that stimulates LM3 cells' proliferation 3-fold more than CARB.…”
Section: Discussionmentioning
confidence: 99%